Problems of organization and financing of high-tech medical care in 2017 - S. I. Kolesnikov (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The authors analyzed the essence of new federal laws, which change some implementation aspects of other basicfederal laws, such as Law on Compulsory Medical insurance in the Russian Federation, Law on Basics of health protection of citizens in the Russian Federation, Budget Code, Tax Code and other legal acts, determining the peculiarities of financing of high technology medical care since January 1, 2017 onwards. The main challenges and risks of Compulsory Medical Insurance Federal Foundation was identified, it becoming the sole holder of the funds intended for the financing of high-tech medical care. The main risk is that federal and regional authorities are not only being excluded from financing, but are losing the role of health care state customer. And in the conditions of financial crisis in the country it will happen. In this case there is a great possibility of financial deficit for high technological medical care in the federal medical scientific institutions. A number of measures for planning indicators of high-tech medical assistance in the scientific medical organizations was proposed. These measures can prevent corruption and defend federal (state) segment of health care system, providing the complex and high level assistance for the most severe ill patients.